Effect of Nickel Slag on the Properties of Cellular Lightweight Concrete - Ahmad, Irma Aswani; Sampebua, Onesimus; Pertiwi, Nurlita; Taufieq, Nur Anny Suryaningsih (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. This study aims to analyze the effect of nickel slag as a partial replacement for fine Aggregate on the mechanical and physical properties of Cellular Lightweight Concrete (CLC). The research employed an experimental laboratory method, with nickel slag contents of 0%, 2.5%, 5%, 7.5%, and 10%. Tests were conducted on compressive strength, flexural strength, and water absorption according to SNI standards. The results show that incorporating nickel slag up to 7.5% increased compressive strength from 0.687 MPa to 1.221 MPa, representing a 77.7% improvement compared to the control mix. The flexural strength remained relatively stable between 1.323 kN and 1.385 kN, indicating that slag addition had no significant effect on flexural behavior. In contrast, water absorption decreased by 24.4%, from 20.575% to 15.544%, suggesting reduced porosity due to the micro-filler effect of fine slag particles. The optimum slag content was 5–7.5%, providing the best balance between mechanical strength and water resistance. Technically and practically, using nickel slag as a partial sand substitute presents a promising approach for developing eco-friendly lightweight concrete, supporting green construction and circular economy concepts